Usaha Peningkatan Pemahaman Siswa dan Mahasiswa dalam Masa Pandemi Covid-19 dengan Video Pembelajaran Menggunakan Aplikasi Kinemaster - Yulia Retno Sari; Deby Erdriani (AJAD : Jurnal Pengabdian kepada Masyarakat, 2022)
Community Service Activities were carried out online with the theme "Creating Cool Learning Videos to Improve Students' Understanding during the Covid-19 Pandemic". This Community Service partnered with teachers and lecturers in the city of Padang. The purpose of carrying out community service activities is to increase teacher knowledge about teaching video maker applications and teachers are able to make interesting teaching videos so that students are motivated to learn and quickly understand the material being taught. The method used is descriptive qualitative. The data used are primary data from webinar participants. From the results of the implementation of community service activities, it can be concluded that this webinar can increase the knowledge of teachers in the city of Padang in presenting teaching materials. And also improve the ability of teachers in making interesting teaching videos using Kinemaster, this is indicated by a graph of the survey evaluation results of 100%.